Talking Back: Shifting the Discourse of Deficit to a Pedagogy of Cultural Wealth of International Instructors in US Classrooms. (June 2014) - Yep, Gust A.
Abstract : Using a combination of critical theory, poststructuralism, and critical pedagogy, this chapter calls for a shift in the ways we conceive, imagine, and represent international instructors in US classrooms. More specifically, it highlights the importance of the voices of international instructors themselves, proposes a shift from the current discourse of deficit to one of cultural wealth, and offers some directions for future research in this area.